Perfil de utilização de medicamentos e qualidade de vida de usuários atendidos em quatro unidades básicas de saúde de Belo Horizonte - Katia Rodrigues Silva (2015)
Studies regarding the use of medicines are important to understand the individual determinants related to its use. The evaluation of the quality of life (QoL) of individuals who use medicines is necessary to understand the influence of this use in QoL. This information may subsidize actions to target health promotion policies and the proper use of medicines. The aim of this study was to evaluate the drug utilization profile and the QoL of individuals attending four public Health Centers (HC) in Belo Horizonte. A cross-sectional study was conducted between 2013 and 2014 with interviews, using a semi-structured questionnaire, to adult individuals registered in one of the four HC. The outcomes were the number of drugs used in the 15 days preceding the interview and the QoL, which was assessed using the WHOQOL-bref instrument. The study included 930 individuals, mostly women (79.9%), with an average age of 45 years and poor education (64.7%). The participants used an average of 2.2 drugs and the prevalence of use was 78%. Having more than two chronic diseases and more than five medical appointments annually were associated with increased use of medicines. Higher age and poorer self-reported health status were related to greater use of medicines in both general and women population. Receiving poor orientation on the health condition and treatment was related to decreased use of medicines in both general and women population. In men population, not having a job and being admitted in a hospital were associated with increased use of medicines. The most used drugs were those for the cardiovascular system (37.9%) and nervous system (29.6%). Individuals who used medicines, regardless of the presence or absence of chronic diseases, presented worse self-perception of QoL, particularly in overall QoL and in the physical domain. The increase in the number of drugs used, regardless of the pharmacological class, was related to lower QoL scores. For the proper use of medicines, it is suggested that groups that use more medications, such as the elderly and people with chronic diseases, receive greater care in HC. The use of medicines, both the quantity and type of class used, showed a negative influence on the individuals perceptions of their QoL. The decrease in QoLs perception in patients using drugs has multidimensional aspects involving their adverse events, the perception of being sick 9 and the loss of autonomy. Strengthen and improve the services provided may promote the rational use of medicines and improve the QoL of individuals.